On the weak convergence of stochastic processes - Banys, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Банис. О слабой сходимости ступенчатых случайных процессов R. Banys. Apie laiptuotų atsitiktinių procesų silpną konvergenciją